2004
DOI: 10.1007/s00432-003-0519-6
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of a gastric transcription factor, Sox2, and ectopic expression of intestinal homeobox genes, Cdx1 and Cdx2: inverse correlation during progression from gastric/intestinal-mixed to complete intestinal metaplasia

Abstract: Down-regulation of Sox2, besides ectopic expression of Cdx genes, may be important factors for the development of IM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
172
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 122 publications
(186 citation statements)
references
References 62 publications
14
172
0
Order By: Relevance
“…Ectopic CDX2 expression was believed related with intestinal metaplasia of the stomach, and Barrett's esophagus(BE) in human beings (Eda et al, 2003;Guo et al, 2004;Shi et al, 2008;Tsukamoto et al, 2004). Silberg DG found that the expression of CDX2 in transgenic mice can lead occurrence of IM in gastric mucosa (Silberg et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ectopic CDX2 expression was believed related with intestinal metaplasia of the stomach, and Barrett's esophagus(BE) in human beings (Eda et al, 2003;Guo et al, 2004;Shi et al, 2008;Tsukamoto et al, 2004). Silberg DG found that the expression of CDX2 in transgenic mice can lead occurrence of IM in gastric mucosa (Silberg et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Ectopic CDX2 expression is considered to involve in the development of intestinal metaplasia and play significant roles in oncogenesis in gastrointestinal tract and its expression has been demonstrated in intestinal metaplasia of the stomach, and Barrett's metaplasia in human beings. So, CDX2 has concerned recently as an early marker for IM epithelium (Eda et al, 2003;Guo et al, 2004;Tsukamoto et al, 2004;Shi et al, 2008). Villin is a tissue-specific actin-binding cytoskeletal protein that is associated with actin filaments in the microvilli and terminal web of epithelial cells.…”
Section: Expression Of Cdx2 and Villin In Gastric Cardiac Intestinal mentioning
confidence: 99%
“…Normally CDX2 is localized to the small and large bowel, 44,45 where it is responsible for the maintenance of intestinal phenotype, 21,22 including the upregulation of MUC2, an intestinal-type mucin, in goblet cells. 31,46 CDX2 expression has also been reported in 54% of gastric carcinomas, often in conjunction with MUC2 expression. 47 In this milieu, CDX2 is associated with tumor progression, during which tumors undergo an immunophenotypic shift from gastric phenotype (MUC5AC and/or MUC6 positive) to intestinal phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…In the process of intestinalization of stomach mucosa, changes in the expression of various genes, especially homeobox genes, have been reported. [44][45][46] Intestinal metaplasia can be caused in transgenic mice with targeted overexpression of Cdx2 in the stomach. 44 Alternatively, intestinal metaplasia may evolve from SPEM through a progressive change in cell mucin and trefoil expression similar to that observed in the ulcer-associated cell lineage by Wright et al 47 The results here suggest that a dynamic process of metaplasia may give rise first to SPEM in the setting of oxyntic atrophy followed by evolution of intestinal metaplasia under the influence of chronic inflammation.…”
Section: Spem Specifically Arises In and Spreads Out From The Intermementioning
confidence: 99%